A Comparative Study to Assess the Efficacy of Salbutamol Nebulization Versus 3% Hypertonic Saline Nebulization among the Under Five Children with Acute Bronchiolitis. A Quasi-Experimental Study. Narrative Review (International Journal of Nursing Education, 2019)
Introduction, Acute bronchiolitis is the most common lower respiratory tract infection affecting the under five children affecting both developed country and undeveloped country. The result of hypertonic nebulization studied by many investigators found to be more effective and helpful to baby with no adverse effect of drugs.1 Aims: The aim of the narrative review is to find the information on effectiveness of salbutamol nebulization and 3% hypertonic saline nebulization in management of under five children with acute bronchiolitis. Methodology: Intervention - nebulization. Type of the study: Comparative study, quasi experimental design, pre experimental, true experimental research design. Type of the participant: Under five children who admitted in the hospital with acute bronchiolitis. Setting of the study: Sharda hospital in pediatrics ward. Outcome- this narrative review shows that 3% hypertonic nebulization is effective, in treatment of acute bronchiolitis based on cost effect, reduce hospital duration and less side effect to salbutamol nebulization.
Keywords: Acute bronchiolitis, salbutamol nebulization, 3% hypertonic nebulization, under five children.